2022
DOI: 10.1186/s12885-022-10199-x
|View full text |Cite
|
Sign up to set email alerts
|

Are anti-PD-1-associated immune related adverse events a harbinger of favorable clinical prognosis in patients with gastric cancer?

Abstract: Background Immune checkpoint inhibitors (ICIs) has shown remarkable benefit in the treatment of a range of cancer types, although it may initiate immune related adverse events (irAEs) in patients. Some studies have shown that there is a close relationship between the occurrence of irAEs and prognosis. In present study, we have attempted to establish whether the occurrence of irAEs after the use of anti PD-1 antibodies is associated with treatment efficacy in people with advanced gastric cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…Several studies have suggested a potential association between irAEs and a more favorable response to immunotherapy in patients [118,119]. Additionally, research has demonstrated a correlation between the occurrence of irAEs following immunotherapy and improved survival outcomes in GC patients [120][121][122]. Furthermore, certain studies have identified potential biomarkers for predicting the occurrence of irAEs [123].…”
Section: Predictive Biomarkers Of Immunotherapy-related Adverse Event...mentioning
confidence: 99%
“…Several studies have suggested a potential association between irAEs and a more favorable response to immunotherapy in patients [118,119]. Additionally, research has demonstrated a correlation between the occurrence of irAEs following immunotherapy and improved survival outcomes in GC patients [120][121][122]. Furthermore, certain studies have identified potential biomarkers for predicting the occurrence of irAEs [123].…”
Section: Predictive Biomarkers Of Immunotherapy-related Adverse Event...mentioning
confidence: 99%
“…irAEs that occur early after treatment initiation are associated with favorable PFS and ORR in NSCLC patients treated with nivolumab [ 150 ]. Patients with gastric adenocarcinoma with irAEs treated with anti-PD-1 antibodies had a longer OS (176 days vs 94 days, P ═ 0.001) than patients without irAEs, and the occurrence of irAEs was an independent favorable prognostic factor in this group [ 152 ].…”
Section: Advances In Predictive Biomarkersmentioning
confidence: 99%
“…IrAEs have been proven to promote the treatment e cacy of ICIs in patients with melanoma, NSCLC, hepatocellular carcinoma, and gastric cancer (Nakamura et al, 2017;Toi et al, 2018;Xu et al, 2021;Zhang et al, 2022). However, the relationship between irAE-related AI and ICIs treatment e cacy has not yet been evaluate owing to the low incidence and concealment of AI.…”
Section: Introductionmentioning
confidence: 99%